The impact of using prestressed CFRP bars on the development of flexural strength - Edan Ahmed Salim; Abdulsahib Wael Shawky (Open Engineering, 2024)
The load-carrying capacity and ductility of conventional steel reinforcement may be greatly increased by using ordinary and prestressed carbon fiber-reinforced polymer (CFRP) bars, resulting in reinforced concrete structures with greater sturdiness. This research investigates the flexural behavior of CFRP-prestressed beams with bonded tendons as opposed to conventional steel-prestressed beams. This article examines a less explored topic that often fails because post-tensioned beams with unbonded CFRP tendons are crushed by concrete. The linear-elastic behavior of CFRP accounts for much of the experimentally observed considerable variations in flexural characteristics between CFRP and steel-prestressed beams. Compared to unbonded CFRP specimens, bonded CFRP specimens are much stronger. Our knowledge of CFRP reinforcement in concrete infrastructure is advanced by this work, which highlights the need for better design techniques to increase strength and ductility. It is recommended that CFRP bars be bonded with epoxy resin to restrict fast energy dissipation and avoid concrete failure. As a result, CFRP-reinforced concrete beams will react less linearly and more ductilely. CFRP may improve prestressed concrete beam performance and lifespan in a number of scenarios, as shown by comparative research with traditional steel reinforcement. Six 1,800–mm-long RC beams with a 200 × 300 mm cross-section were examined and divided into three groups, analyzing important loading phases (i.e., cracked, ultimate, and mid-span deflection) using CFRP bars as prestressed tendons to replace the bottom steel rebars. The load-carrying capabilities and ductility of CFRP-reinforced beams were much greater than those of the reference beam. A single beam using normal CFRP bars for reinforcement showed a 21.2 mm mid-span deflection and an ultimate load of 157.2 kN, with a 57.7-kN fractured load. Another beam with normal CFRP bars also showed enhanced performance, with a mid-span deflection of 21.2 mm, an ultimate load of 160.6 kN, and a cracking load of 57.5 kN.